EFEKTIVITAS TERAPI SPRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Murni, - (Sistem Informasi, 2018)
Spritual emotional freedom technique (SEFT) is technique of relaxation mind-body therapy. SEFT is a merging technique of the bodys energy system (energy medicine) and spiritual therapy using tapping method on the body specific points. The aims of this research is to determine the effectiveness of spritualemotional freedom technique therapy to decrease blood pressure in hipertensive patients in Puskesmas Harapan Raya Pekanbaru. Design of the research used quasy experiment. The sample of research were 60 peoples, 30 as experimental group and 30 as control group. The technique for sampling used purposive sampling. Data Analysis was used dependent and independent sample T test. The results showed that there was significant influence between therapy SEFT with decrease blood pressure in hypertensive patients with p <0.05 (p = 0.000). It is suggested to use SEFT therapy as an alternative treatment of hypertension.